Trade policy and health: from conflicting interests to policy coherence - Chantal Blouin
Policy incoherence at the interface between trade policy and health can take many forms, such as international trade commitments that strengthen protection of pharmaceutical patents, or promotion of health tourism that exacerbates the shortage of physicians in rural areas. Focusing on the national policy-making process, we make recommendations regarding five conditions that are necessary, but not sufficient, to ensure that international trade policies are coherent with national health objectives. These conditions are: space for dialogue and joint fact-finding; leadership by ministries of health; institutional mechanisms for coordination; meaningful engagement with stakeholders; and a strong evidence base.